Towards an aesthetic of dalit literature:history controversies and considerations - Sharankumar Limbale; Mukherjee, Alok (Hyderabad Orient BlackSwan, 2018)
"This book, the first critical work by an eminent Dalit writer to appear in English, is a provocative and thoughtful account of the debates among Dalit writers on how Dalit literature should be read. This book includes an extensive interview with the author, an exhaustive bibliography, and a critical commentary by the translator. Originally published in Marathi, this is the first English translation of the book."--Provided by publisher.
Keywords: Dalit Literature and Ambedkarism; Dalit Literature and Marxism